Joint optimization of preventive maintenance and spare parts inventory for an optimal production plan with consideration of CO2 emission. (May 2016) - Ba, Kader; Dellagi, Sofiene; Rezg, Nidhal; Erray, Walid
Abstract: This article presents a joint optimization of spare parts inventory and preventive maintenance. While minimizing CO2 emissions, this approach is based on an optimal production plan achieved thanks to the HMMS model. The process which is studied in this paper only manufactures one type of product. The purpose of the paper is to determine for a random demand over a given period, a cost-effective production plan and a maintenance policy which integrates a spare parts strategy in accordance with environmental requirements and regulations. Our green spare parts management can be defined as a set of actions that are applied in order to decrease the spare parts footprint in its lifetime (Ba et al., 2015)[1] . Indeed, we take into account the spare parts characteristics (new or used) which will be used during maintenance actions (preventive or corrective) to preserve the environment. Consequently, we set up analytical models based on the effect of the production rate on the system deterioration so as to substantially cut the maintenance costs, production costs and CO2 emissions. To evaluate the performance of our models, we give some illustrative examples. Highlights: Establishment of an optimal production plan for a manufacturing process. Cost-effective maintenance strategy with a green spare parts strategy. Possibility to choose between used and new spare parts to execute maintenance action.